2009
DOI: 10.2478/s11658-008-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors and their role in carcinogenesis and anti-tumor treatment

Abstract: Toll-like receptors (TLRs) have been described as major components of the innate immune system, recognizing the conserved molecular structures found in the large groups of pathogens called pathogen-associated molecular patterns (PAMPs). TLR expression is ubiquitous, from epithelial to immunocompetent cells. TLR ligation triggers several adapter proteins and downstream kinases, leading to the induction of key pro-inflammatory mediators but also anti-inflammatory and anti-tumor cytokines. The result of this acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 113 publications
(100 reference statements)
2
42
0
1
Order By: Relevance
“…However, aberrant inactivation of NFkB through deletion of its essential modulator (NEMO, NF-kB essential modulator) triggers chronic inflammation and spontaneous HCC development (31). Likewise, TLRs, key players in innate immunity to pathogens and ubiquitously expressed on cancer cells, also play a complex role in regulating inflammation and tumorigenesis (35,36). Given the regulatory role in the activation of the TLR and NFkB pathways, we assume that MAP4K4 might represent a promising therapeutic target for chronic liver inflammation and associated cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, aberrant inactivation of NFkB through deletion of its essential modulator (NEMO, NF-kB essential modulator) triggers chronic inflammation and spontaneous HCC development (31). Likewise, TLRs, key players in innate immunity to pathogens and ubiquitously expressed on cancer cells, also play a complex role in regulating inflammation and tumorigenesis (35,36). Given the regulatory role in the activation of the TLR and NFkB pathways, we assume that MAP4K4 might represent a promising therapeutic target for chronic liver inflammation and associated cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the anti-tumor roles of TLR4 have also attracted much attention. TLR ligands might enhance antigen presentation or induce the expression of target molecules, and bring into play the functions of immune response against tumor growth (29). However, what will occur in SW620 cell followed by TLR4 activation?…”
Section: Discussionmentioning
confidence: 99%
“…More evidence indicated that TLR signaling could enhance the anti-cancer immunity and the molecules involved in this pathway were often used as targets for therapy against cancer, although there were reports that expression of TLR could lead to tumor progression (Wolska et al, 2009). Many TLR agonists were proved to be helpful for the treatments of various kinds of cancer (Salaun et al, 2006;Zhang et al, 2009;Cheng and Xu, 2011;Lin et al, 2011;Zhang et al, 2011), and TLR5 agonist was reported to result in significant tumor regression (Rhee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%